PENGARUH PENDIDIKAN, KESEHATAN, USIA DAN UPAH TERHADAP PRODUKTIVITAS TENAGA KERJA DI DKI JAKARTA - Chika Chairunnisa; Indri Arrafi Juliannisa (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2022)
This study aims to determine the effect of education level, health level, age and wage level on labor productivity. This study uses the province of DKI Jakarta. The sample used was from 19991-2020 of which the total sample was 30. The data in this study is secondary data obtained from BPS DKI Jakarta. Hypothesis testing using Time Series Analysis using the Eviews 9 program with a significance level of 5% (0.05). The results of the data partially show that age and wage levels have a positive effect on labor productivity, while education and health levels have no effect on labor productivity. And simultaneously all the existing variables together affect labor productivity.